THU0143 Cholesterol efflux capacity of hdl is otherwise improved by different biologic-dmards in rheumatoid arthritis. (15th June 2017) - Cacciapaglia, F; Perniola, S; Härdfeldt, J; Nivuori, M; Magazzino, O; Giannotta, MG; Giannini, M; Anelli, MG; Moschetta, A; Iannone, F
Abstract : Background: Rheumatoid arthritis (RA) patients have an increased mortality for cardiovascular (CV) events, not completely explained by impaired cholesterol levels or other traditional CV risk factor (1). Target therapy with effective control of systemic inflammation have been demonstrated to improve articular outcomes, but the effect on CV risk is still under investigation (2). The ability of high-density lipoprotein (HDL) to accept cholesterol from macrophages (HDL cholesterol efflux capacity; HDLc-EC) is a key step in reverse cholesterol transport, with significant consequences on incident atherosclerotic CV disease (3), but this marker in RA have still alternate evidence (4, 5). Objectives: To assess the effects of different biological DMARDs on HDLc-EC in RA Methods: Disease activity data and blood samples from 40 patients with RA before and up to 12 months after starting a biologic therapy were collected. The study included patients starting intravenously administered Abatacept (ABA;n=10), Infliximab (INF;n=10), Tocilizumab (TCZ;n=10), and Rituximab (RTX;n=10), at approved dose regimens for RA treatment. HDLc-EC was measured on paired serum samples using THP-1 macrophages and a fluorometric assay for cholesterol measurement. ANOVA was used to compare paired continuous data, and Pearson' r value was calculated for correlations. Results: Disease activity assessed by DAS28-CRP and CDAI significantly dropped during all treatments. No significant changes in total and high or light density cholesterol fractions were detected. HDLc-EC at baseline was 22±3% with a statistically significant increase up to 25±3% and 27±4% after 6 and 12 months of treatment, respectively (P<0.001) [Figure A]. Patients treated with INF and RTX demonstrated the higher rise in HDLc-EC, already after 6 months and lasting up to 12 months of treatment. ABA and TCZ treated patients after 6 months had a slight HDLc-EC rising, with a subsequent plateau. We observed an opposite correlation between HDLc-EC and disease activity by DAS28-CRP and CDAI (r=-0.2;P=0.01) [Figure B]. Finally, no CV events were detected during the study follow-up. Conclusions: Biologic treatment can influence the HDLc-EC of RA patients, already after 6 months of therapy, and is associated with changes in disease activity and inflammatory status. Infliximab and Rituximab seem to have an enhanced impact on HDLc-EC. Future studies need to address the mechanisms beyond these intriguing findings. References: Arts EE et al. Ann Rheum Dis. 2015;74:998–1003. Woodworth TG, den Broeder AA. Best Pract Res Clin Rheumatol. 2015;29:543–9. Rohatgi A. et al. N Engl J Med 2014;371:2383–93. Liao KP et al. J Am Heart Assoc. 2015;4(2). Ormseth MJ. et al. Arthritis Rheumatol. 2016;68:2099–105. Disclosure of Interest: None declared